Frequency and incidence of arterial events in patients with venous thromboembolism compared to the general population: A systematic review and meta-analysis of cohort studies. Issue 203 (July 2021) - Noumegni, Steve Raoul; Hoffmann, Clément; Tromeur, Cécile; Lacut, Karine; Didier, Romain; Couturaud, Francis; Bressollette, Luc
Abstract: Background: Recent literature hypothesized that patients with venous thromboembolism (VTE) are at increased risk of developing arterial ischemic events than general population without VTE. However, data summarizing the epidemiology of arterial events among VTE population compared to the general population are lacking. Methods: We conducted a systematic review and meta-analysis from current literature. PubMed, EMBASE, and Cochrane databases were searched between Jan 1, 2000, and December 31, 2020. Eligible studies were observational cohort studies published in English on arterial ischemic events in patients with VTE. Pooled effect size estimates and their 95% confidence intervals were obtained through random-effect models meta-analysis. Results: Twenty-eight observational studies enrolling 352, 014 patients were identified and included. The pooled frequency of all arterial events was 6.1% (95% CI: 3.7–9.1) in patients with VTE and was significantly higher than the pooled frequency of 5.0% (95% CI: 3.1–7.2) found in controls, with a pooled risk ratio (RR) of 1.20 (95% CI: 1.01–1.44; p = 0.0422). The pooled incidence of all arterial events in patients with VTE was 11.3‰ per patient-year (95% CI: 4.6–18.0), and was significantly higher than the 9.2‰ per patient-year (95% CI: 2.0–16.4) obtained in controls (Incidence rate ratio, IRR: 1.32; 95% CI: 1.08–1.61; p = 0.0103). The pooled frequency and pooled incidence of arterial events were also higher in patients with unprovoked VTE than in patients with provoked VTE (RR: 2.12; 95% CI: 1.38–3.24; p = 0.0042; and IRR: 2.26, 95% CI: 1.45–3.49; p = 0.0032). Conclusion: The frequency and incidence of arterial events in patients with VTE are considerably higher than in the general population, without VTE. Further studies are urgently needed to understand these differences and reduce the burden related to these diseases. Funding: None. Highlights: The risk of arterial events is higher in patients with venous thromboembolism (VTE), than in the general population. This over-risk is confirmed in patients with unprovoked VTE compared to the general population. This over-risk seems to disappear considering patients with provoked VTE compared to the general population. The risk of arterial events is also higher in patients with unprovoked VTE than in patients with provoked VTE.